The unromantic orient - Asad, Muhammad (Islamic Book Trust, 2004)
This first English translation of a long forgotten work recaptures his initial experiences in an unknown and intriguing land where he found a new home and a new sense of belonging. "The Unromantic Orient" is not only an impressionistic journal of a young man in search of certitude, it also provides insights into the spiritual transformation of Leopold Weiss who would soon convert to Islam and spend the rest of his life in studying and writing about it. The travelogue starts at the Jerusalem train station and takes us through Cairo, Amman, parts of the TransJordan, Palestine, Damascus and Istanbul.